2011
DOI: 10.1080/0972060x.2011.10643924
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwaves on Essential oils of White and Black Pepper (Piper nigrumL.) and their Antioxidant Activities

Abstract: White and black peppers were subjected to conventional roasting as well as microwave heating in order to study the effects of such techniques on the volatile constituents of each spice oil and its antioxidative activity. Hydrodistillation oil of each spice was analyzed using Gas Chromatography (GC) and Gas chromatography-Mass spectrometry (GC-MS). Twenty six compounds were identified in essential oil of white pepper, whereas, twenty compounds were detected in black pepper essential oil. δ-Carene, limonene, αan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
2
8
1
Order By: Relevance
“…3). In our previous study we proved that microwave heated samples of HD oregano leaves essential oil have the stronger antioxidant effect for reduction of DPPH radical and bleaching of β-carotene than conventionally roasted samples due to the higher percentages of two major isomeric phenols carvacrol and thymol and their biosynthetic precursors γ-terpinene and p-cymene in microwave heated sample (44.5 %) than in conventionally roasted sample (33.7 %) 46 , also we proved that α and β-pinene, compher and camphene may attribute to antioxidant activity of black pepper oil 47 . In our previous study we proved that microwave heated samples of HD oregano leaves essential oil have the stronger antioxidant effect for reduction of DPPH radical and bleaching of β-carotene than conventionally roasted samples due to the higher percentages of two major isomeric phenols carvacrol and thymol and their biosynthetic precursors γ-terpinene and p-cymene in microwave heated sample (44.5 %) than in conventionally roasted sample (33.7 %) 46 , also we proved that α and β-pinene, compher and camphene may attribute to antioxidant activity of black pepper oil 47 .…”
Section: Resultssupporting
confidence: 52%
“…3). In our previous study we proved that microwave heated samples of HD oregano leaves essential oil have the stronger antioxidant effect for reduction of DPPH radical and bleaching of β-carotene than conventionally roasted samples due to the higher percentages of two major isomeric phenols carvacrol and thymol and their biosynthetic precursors γ-terpinene and p-cymene in microwave heated sample (44.5 %) than in conventionally roasted sample (33.7 %) 46 , also we proved that α and β-pinene, compher and camphene may attribute to antioxidant activity of black pepper oil 47 . In our previous study we proved that microwave heated samples of HD oregano leaves essential oil have the stronger antioxidant effect for reduction of DPPH radical and bleaching of β-carotene than conventionally roasted samples due to the higher percentages of two major isomeric phenols carvacrol and thymol and their biosynthetic precursors γ-terpinene and p-cymene in microwave heated sample (44.5 %) than in conventionally roasted sample (33.7 %) 46 , also we proved that α and β-pinene, compher and camphene may attribute to antioxidant activity of black pepper oil 47 .…”
Section: Resultssupporting
confidence: 52%
“…Plant extracts and secondary metabolites possessed antifungal, antiviral, or antimicrobial activities. The main constituents of black pepper were piperine and volatile oils (Abd El Mageed et al 2011). High Performance Liquid Chromatography analysis revealed that piperine, piperidine, eugenol, and catechin were constituents of Piper nigrum crude extract (Jin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Piperine is the main component that causes edible flavor in pepper (Nitin et al 2012). Pepper essential oils have potential for biopesticide agent (Abdullah et al 2020), antibacterial agent (Abdallah & Abdalla 2018), analgesic (Costa et al 2016), and natural insecticide (Chaubey, 2017), as well as antioxidant activity (Gülçin, 2005;Abd El Mageed et al 2011).…”
Section: Introductionmentioning
confidence: 99%